Systematization of the past tense of English irregular verbs in twelve graders at the University College - Román Fernández, Alain (Universidad Central Marta Abréu de las Villas, 2020)
The major paper entitled Systematization of the past tense of English irregular verbs was designed and partially implemented in a twelve grade group of students at the University Colleague, with the objective of systematizing this verb tense to have the students ready to interact and communicate in the English lessons. Different empirical methods were administered to verify the problematic situation declared in the introduction of this paper as well as some theoretical methods to process the data obtained and the theoretical information consulted. Some necessary theoretical and methodological bases about the teaching of English as a foreign language, grammar and the past tense of English irregular verbs suggested by different authors were analyzed. The proposal of the activities was designed taking into account the results of the diagnosis. It was partially implemented and all the activities were performed satisfactorily. Though, the results were not as satisfactory as it was expected, the students were able to communicate intelligible with their classmates, and they were motivated to participate during the lessons. The dialectic materialistic general method was followed, as well as the quantitative approach, mainly the pretest and posttest design
Keywords: Educación Superior; Educación; Lenguas Extranjeras; Didáctica del Idioma; Enseñanza del Inglés